Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

So far I got here

\begin{align} (r\cos\phi)^2 & + 6 r \sin\phi- 9 = 0\\ (r\cos\phi)^2 & = 9 - 6r \sin\phi \end{align}

share|cite|improve this question
Where is the question then? – awllower Feb 5 '13 at 7:47
I am not in class rather stuck on problem – user1530249 Feb 5 '13 at 8:11

Since $r^2\cos^2(\phi)+6r\sin(\phi)-9=0$, $$ \begin{align} r &=\frac{-6\sin(\phi)\pm\sqrt{36\sin^2(\phi)+36\sin^2(\phi)}}{2\cos^2(\phi)}\\ &=\frac{-3\sin(\phi)\pm3}{\cos^2(\phi)}\\ &=\frac3{\sin(\phi)\pm1} \end{align} $$ Note that both '$+$' and '$-$' yield the same curve. '$-$' simply gives the curve $180^\circ$ around with negative the radius. So we can simply pick '$+$': $$ r=\frac3{1+\sin(\phi)} $$

share|cite|improve this answer

You could also solve for $r$ as a function of $\theta$: write $\cos^2(\theta)$ in terms of $\sin(\theta)$, put all terms on the left, and factor. You should end up with $$ r = \frac{3}{1+\sin(\theta)}$$

share|cite|improve this answer
Thanks this is the right answer. Could you explain how you went from r2cos2(θ)+6rsin(θ)=9 to the answer you posted above? – user1530249 Feb 5 '13 at 8:25
@user1530249: we have $r^2\cos^2(t)+6r\sin(t)-9=0$. $\cos^2(t)=1-\sin^2(t)$, so $r^2(1-\sin^2(t))+6r\sin(t)-9=0$, so $r^2-r^2\sin^2(t)+6r\sin(t)-9=0$. This is a quadratic equation and can be solved easily. – Babak S. Feb 5 '13 at 12:57


As always we choose $x=r \cos \theta$ and $y=r \sin \theta$

Thus $$(r \cos \theta)^2 +6r \sin \theta -9=0$$

With the identity $\cos^2 \theta = 1- \sin^2 \theta$ we find

$$r^2 - (r \sin \theta)^2 + 6r \sin \theta -9=0$$

Which equals $$(r \sin \theta -3)^2=r^2$$

Thus $r=r \sin \theta -3$ or $r= 3-r \sin \theta$ and subsequently we see $$r=\frac{3}{\sin \theta - 1} \lor r=\frac{3}{1+ \sin \theta} $$

share|cite|improve this answer
Note that both $r=\frac3{\sin(\theta)-1}$ and $r=\frac3{1+\sin(\theta)}$ represent the same points, but at $\theta$ for one and $\theta+\pi$ for the other. – robjohn Feb 5 '13 at 16:29

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.